Assessment of Fisheries Management Status with Ecosystem Approach on Bagan Boat Ship in Bungus Waters - Silaban, Recyka; Yani, Alit Hindri; Brown, Arthur (Journal of Coastal and Ocean Sciences, 2023)
EAFM or Ecosystem Approach for Fisheries Management is a concept of how to balance socio-economic goals in fisheries management while still considering knowledge, information and uncertainty about biotic, abiotic and human interactions in aquatic ecosystems through a comprehensive and sustainable integrated fisheries management. The fishery potential is quite large in Bungus waters and the continuous fishing activities carried out by boat lift fishermen lead to overfishing; therefore fisheries management is very necessary to realize sustainable fisheries, especially for fishery commodities. The purpose of this study was to determine the status of the management of the bagan boat fishery in Bungus pps. This research was conducted in February 2022 at the Samudra Bungus Fishing Port, West Sumatra. The method used in this study uses the method issued by the National Working Group EAFM.DIT SDI KKP; the data taken are primary data and secondary data. Analysis of the data used using an ordinal-based likert scoring with a scoring assessment of 1,2,3. The greater the value, the better the EAFM that has been run. The results of the study show that the management of capture fisheries in the fishing technique domain at PPS Bungus is still lacking in implementing EAFM with a composite value of 18.8